Manajemen Rekrutmen dan Pengembangan Sumber Daya Manusia (SDM) Pengajar dalam Menghadapi Standardisasi Pendidikan Modern di Pondok Pesantren Al Ikhlas Modern Pasuruan - Wahyudi Widodo (MASALIQ, 2026)
The importance of managing the recruitment and development of teaching human resources (HR) in improving educational quality has become a strategic issue, especially in facing modern educational standardization within the pondok pesantren environment. This study aims to analyze the recruitment and development processes of teaching human resources and to identify the obstacles encountered in meeting modern educational standards at Pondok Pesantren Al Ikhlas Modern Pasuruan. This study employed a qualitative approach with a descriptive research type. The data were obtained through interviews, observation, and documentation, and were then analyzed using an interactive analysis technique comprising data reduction, data display, and conclusion drawing. The results showed that the teacher recruitment process already had several stages, but it was still dominated by a traditional approach and was not yet fully competency-based. The development of teaching human resources had also been carried out, but it remained incidental and focused more on religious aspects than on strengthening pedagogical and technological competencies. In addition, limited facilities and the absence of a structured system became the main obstacles to improving teacher quality. This study concludes that improvements in a more comprehensive and sustainable human resource management system are needed so that the pondok pesantren can meet the demands of modern education more effectively.